Delayed initiation of antiretroviral therapy among HIV-discordant couples in Kenya - Kahn, Talia R. (2012)
Timely initiation of antiretroviral therapy (ART) is particularly important for HIV-discordant couples because viral suppression greatly reduces the risk of transmission to the uninfected partner. To identify issues and concerns related to ART initiation among HIV-discordant couples, we recruited a subset of discordant couples participating in a longitudinal study in Nairobi to participate in in-depth interviews and focus group discussions about ART. Our results suggest that partners in HIV-discordant relationships discuss starting ART, yet most are not aware that ART can decrease the risk of HIV transmission. Additionally, their concerns about ART initiation include side effects, sustaining an appropriate level of drug treatment, HIV/AIDS related stigma, medical/biological issues, psychological barriers, misconceptions about the medications, the inconvenience of being on therapy, and lack of social support. Understanding and addressing these barriers to ART initiation among discordant couples is critical to advancing the HIV “treatment as prevention” agenda.